O brincar na transição da educação infantil para o ensino fundamental: uma análise das narrativas de crianças - Nois, Letícia Joia de (Universidade Federal de São Carlos, 2021)
This research focuses on the study of the transition from early childhood education to elementary education and to support this study, we worked with authors from the history of childhood and the history of education on the concept of childhood and children since the Middle Ages, both in the Europe as in Brazil, until today and, as these concepts are also treated in the official documents of Brazilian education. In addition, the authors of historical cultural psychology contributed to an elucidation of the child's learning and development process. Such research intends to answer the following questions: What happens in relation to playfulness when the child enters the first year of elementary school? Is there a difference between playing in the last year of Early Childhood Education and playing in the first year of Elementary School, based on testimonies of children's narratives? Given this, this research aims to know, examine and understand through children's narratives, the transition process from early childhood education to elementary education with regard to playfulness in the school environment. To achieve this goal, the field research methodology was qualitative, using semi-structured interviews with 13 children, who participated in the collection process in two stages, the first in the last year of early childhood education and the second in the first year of teaching. fundamental. From interviews conducted, from the perspective of oral narratives and based on the content analysis of Bardin (1979), 4 categories were formulated a posteriori. The first category called "Physical Education" presents and discusses registration units about the physical education classes that appeared in children's narratives, the second category, called "Playful Culture", organizes the results of the registration units: playing with water and / or pool, games with fantasy, games of catch, hide and seek and with sand and also the so-called “wooden toy”. The third was called “Curricular Components” and addresses the registration units for teaching and learning activities carried out by children, using the “activity” registration unit and, finally, the last category entitled “Differences between early childhood education” and elementary education ”brings the registration units that reflect the differences between the stages of basic education according to the children's narratives, being these registration units: recreation; computer classes; playground, and some other registration units, mentioned only once, but which bring important messages to answer the questions of this research. Finally, in the final considerations, the contributions of this study to the school education of children and their possible consequences are treated.
Playing in the transition from early childhood education to primary education: an analysis of children's narratives
Keywords: Escola - instituição; Educação infantil; 1º ano do ensino fundamental; Criança; Lúdico; School – institution; Chil education; Elementar school; Child; Playfulness.; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM